The Monetary Gold Principle under the Jurisdiction of the International Court of Justice - Fadhil, Jomana; Abid, Mustafa (Journal of Legal Sciences, 2026)
The principle of discretionary gold is a procedural legal base established through the judicial practice of the International Court of Justice, as it has been applied outside the International Court of Justice before other international courts, according to which the courts are prohibited from deciding the case brought before them if there is an indispensable third party because his interests are fundamentally affected With the decision that will be issued by the court, as the principle of monetary gold protects third parties who did not appear before the court, and several foundations have been put forward to justify the principle of monetary gold. The principle within the judicial practice of the International Court of Justice in this topic.